Sleep Restriction and Recurrent Circadian Disruption Differentially Affects Blood Pressure, Sodium Retention, and Aldosterone Secretion - McMullan, Ciaran J.; McHill, Andrew W.; Hull, Joseph T.; Wang, Wei; Forman, John P.; Klerman, Elizabeth B. (Frontiers in Physiology, 2022)
Prolonged exposure to chronic sleep restriction (CSR) and shiftwork are both associated with incident hypertension and cardiovascular disease. We hypothesized that the combination of CSR and shiftwork’s rotating sleep schedule (causing recurrent circadian disruption, RCD) would increase blood pressure, renal sodium retention, potassium excretion, and aldosterone excretion. Seventeen healthy participants were studied during a 32-day inpatient protocol that included 20-h “days” with associated scheduled sleep/wake and eating behaviors. Participants were randomly assigned to restricted (1:3.3 sleep:wake, CSR group) or standard (1:2 sleep:wake, Control group) ratios of sleep:wake duration. Systolic blood pressure during circadian misalignment was ∼6% higher in CSR conditions. Renal sodium and potassium excretion showed robust circadian patterns; potassium excretion also displayed some influence of the scheduled behaviors (sleep/wake, fasting during sleep so made parallel fasting/feeding). In contrast, the timing of renal aldosterone excretion was affected predominately by scheduled behaviors. Per 20-h “day,” total sodium excretion increased, and total potassium excretion decreased during RCD without a change in total aldosterone excretion. Lastly, a reduced total renal sodium excretion was found despite constant oral sodium consumption and total aldosterone excretion, suggesting a positive total body sodium balance independent of aldosterone excretion. These findings may provide mechanistic insight into the observed adverse cardiovascular and renal effects of shiftwork.